1998
DOI: 10.1111/j.1559-1816.1998.tb01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Identity, Self‐Esteem, and Values in Dominicans, Puerto Ricans, and African Americans

Abstract: This study investigates the relationship between ethnic identity, self‐esteem, value orientations, and perceived value congruence in 207 minority students. It also investigates within‐group concordance and cross‐cultural differences in value orientations. Dilemmas were used to measure value orientations and perceived congruence between personal and group values. A version of the Multigroup Ethnic Identity Measure (Phinney, 1992) and Rosenberg's Self‐Esteem Scale (1965) were used to measure ethnic identity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
1
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 38 publications
(21 reference statements)
6
48
1
1
Order By: Relevance
“…Conversely, those who have a less well-defined ethnic identity report more symptoms of anxiety and depression (Brittian, Umaña-Taylor, Lee et al, 2013;Yip, Seaton, & Sellers, 2006). Findings have been consistent across studies focused on specific ethnic groups, including Hispanic Americans (e.g., Cronin, Downloaded by [University of Otago] at 09:43 02 October 2015 Levin, Branscombe, van Laar, & Tropp, 2012), Asian Americans (e.g., Lee, Yun, Yoo, & Nelson, 2010;Tran & Lee, 2010), and African Americans (e.g., Lorenzo-Hernández & Ouellette, 1998). In fact, a meta-analysis of 184 studies revealed a moderate association between ethnic identity and the well-being of ethnic minority individuals (r = .17), although stronger effect sizes were found with measures of positive well-being (i.e., self-worth) as compared to maladaptive functioning (i.e., depressive symptoms; Smith & Silva, 2011).…”
Section: Ethnic Identitymentioning
confidence: 77%
“…Conversely, those who have a less well-defined ethnic identity report more symptoms of anxiety and depression (Brittian, Umaña-Taylor, Lee et al, 2013;Yip, Seaton, & Sellers, 2006). Findings have been consistent across studies focused on specific ethnic groups, including Hispanic Americans (e.g., Cronin, Downloaded by [University of Otago] at 09:43 02 October 2015 Levin, Branscombe, van Laar, & Tropp, 2012), Asian Americans (e.g., Lee, Yun, Yoo, & Nelson, 2010;Tran & Lee, 2010), and African Americans (e.g., Lorenzo-Hernández & Ouellette, 1998). In fact, a meta-analysis of 184 studies revealed a moderate association between ethnic identity and the well-being of ethnic minority individuals (r = .17), although stronger effect sizes were found with measures of positive well-being (i.e., self-worth) as compared to maladaptive functioning (i.e., depressive symptoms; Smith & Silva, 2011).…”
Section: Ethnic Identitymentioning
confidence: 77%
“…The model has received quite some empirical support, including from studies that have examined MULTICULTURAL RECOGNITION 171 self-esteem among racial and ethnic minority groups (see Schmitt & Branscombe, 2002). Several other studies with various ethnic groups, including majority groups, have also found positive associations between ethnic identity and self-esteem (e.g., Lorenzo-Herna´ndez & Ouellette, 1998;Martinez & Dukes, 1997;Negy, Shreve, Jensen, & Uddin, 2003). Thus, there are good reasons as well as strong evidence for a positive association between ethnic identity and self-esteem.…”
Section: The Self-esteem Argument Of Multiculturalismmentioning
confidence: 80%
“…The RSES has been used extensively with different ethnic groups, particularly Spanish speaking adolescent groups (Banos & Guillen, 2000;Fernandez & Castro, 2003;Lorenzo-Hernandez & Oullette, 1998;Orshan, 1999;Phinney, Cantu & Kurtz, 1997). From a sample of 120 Mexican American teenagers, Joiner and Kashubeck (1996) reported a Cronbach's alpha coefficient of .87.…”
Section: Rosenberg Self-esteem Scalementioning
confidence: 99%